One-dimensional hexagonal boron nitride conducting channel - Park, Hyo Ju (2020)
Hexagonal boron nitride (hBN) is an insulating two-dimensional (2D) material with a large bandgap. Although known for its interfacing with other 2D materials and structural similarities to graphene, the potential use of hBN in 2D electronics is limited by its insulating nature. Here, we report atomically sharp twin boundaries at AA′/AB stacking boundaries in chemical vapor deposition–synthesized few-layer hBN. We find that the twin boundary is composed of a 6′6′ configuration, showing conducting feature with a zero bandgap. Furthermore, the formation mechanism of the atomically sharp twin boundaries is suggested by an analogy with stacking combinations of AA′/AB based on the observations of extended Klein edges at the layer boundaries of AB-stacked hBN. The atomically sharp AA′/AB stacking boundary is promising as an ultimate 1D electron channel embedded in insulating pristine hBN. This study will provide insights into the fabrication of single-hBN electronic devices.